Production and Publication of Second-Specialty Theses in Medical Technology: A Bibliometric Analysis - Quispe-Aranda, David German (2026)
Objectives This study analyzes the production and publication of second-specialty theses in Medical Technology at the Universidad Nacional Federico Villarreal, aiming to identify methodological and thematic characteristics, as well as determine the proportion of theses that have been published. Methods A bibliometric analysis with an observational, descriptive, and retrospective design was conducted, reviewing 134 theses from 2016 to 2024. To identify publications derived from these theses, searches were performed in Scopus, Web of Science, and Google Scholar, applying optimized search strategies. Results The majority of the theses belonged to the Laboratory specialty (53.8%), followed by Radiology (23.1%) and Therapy (23.1%). Only four theses (2.98%) were published as scientific articles in indexed journals. The publications were found in journals indexed in Scopus, PubMed, SciELO, and Web of Science, with one in Q1 and another in Q3. The study highlights a low conversion rate of theses into scientific articles and underscores the need to strengthen strategies to promote publication, such as adapting theses to article format, implementing institutional incentives, and providing training in scientific writing. Discussion The low publication rate of second-specialty theses in Medical Technology (2.98%) reflects the limited dissemination of knowledge generated at this academic level. To increase scientific output in this field, it is recommended to encourage thesis publication through strategies such as adapting theses into articles, institutional incentives, and training in scientific writing.